Adolescents, Graduated Autonomy, and Genetic Testing. (23rd February 2012) - Fox, Susan
Abstract : Autonomy takes many shapes. The concept of "graduated autonomy" is conceived as comprising several unique features: (1) it is incremental, (2) it is proportional, and (3) it is related to the telos of the life stage during which it occurs. This paper focuses on graduated autonomy in the context of genetic testing during adolescence. Questions can be raised about other life stages as well, and some of these questions will be addressed by discussing a possible fourth characteristic of graduated autonomy, that is, its elasticity. Further scholarship and analysis is needed to refine the concept of graduated autonomy and examine its applications.